Tissue Engineering in Regenerative Medicine - Bernstein, Harold S. (Stem Cell Biology and Regenerative Medicine,, 2011)
Over the past decade, significant advances in the fields of stem cell biology, bioengineering, and animal models have converged on the discipline of regenerative medicine. This volume provides a state-of-the-art report on tissue engineering toward the goals of tissue and organ restoration and regeneration. Examples from different organ systems are used to illustrate progress with growth factors to assist in tissue remodeling; the capacity of stem cells for restoring damaged tissues; novel synthetic biomaterials to facilitate cell therapy; transplantable tissue patches that preserve three-dimensional structure; synthetic organs generated in culture; aspects of the immune response to transplanted cells and materials; and the development of suitable animal models for non-human clinical trials. Throughout the chapters, the reader will observe a common theme of basic discovery informing clinical translation, and clinical studies in animals and humans guiding subsequent experiments at the bench.